Evaluation of antimycobacterial rhamnolipid production from non-cytotoxic strains of Pseudomonas aeruginosa isolated from rhizospheric soil of medicinal plants - Mishra, Alok K; Dubey, Rikesh K; Yabaji, Shivraj M; Jaiswal, Swati (International Journal of Biological Research, 2016)
Rhamnolipids (RLs) are the bacterial derived biosurfactants and known for a wide range of industrial and therapeutic applications. They exhibit potent anti-bacterial activity against various gram positive, gram negative and acid fast bacteria including Mycobacterium tuberculosis. Since, Pseudomonas is one of the largest known genuses containing a variety of rhamnolipid producing strains. Therefore, in this study, we selectively isolated the Pseudomonas aeruginosa strains from the rhizospheric soil of the Indian plants of medicinal value, e.g. Azadirachta Indica and Ficus spp., and evaluated them for their natural ability to produce antibacterial rhamnolipids. The bacteria were identified on the basis of 16s rRNA sequencing and biochemical characterization. Among 33 of P. aeruginosa isolates from different soil samples, four isolates showed potent inhibitory activity against methicillin resistant Staphylococcus aureus (MRSA) and fast grower mycobacterial spp. The inhibitory potential of the isolates was found to be correlated with their ability to produce RLs in the medium. The industrial viability of the strains was assessed on the basis of cytotoxicity determining alternative allele, exoS/exoU and cell mediated cytotoxicity against murine macrophages J774.1. The newly isolated strains harbor exoS allele and exhibits lower cell mediated cytotoxicity on macrophage cell line as compared to the clinical strains PA-BAA-427 and PA-27853 used as a control in this study.Evaluation of antimycobacterial rhamnolipid production from non-cytotoxic strains of Pseudomonas aeruginosa isolated from rhizospheric soil of medicinal plants